Advancing science literacy on viruses through PBL-SETS with interactive multimedia: Effectiveness and students’ voices - Hasan Subekti; Siti Addinul Nasihah; Isnawati Isnawati; Suyidno Suyidno; Heribertus Amaunut Colo (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
This research is necessary because it explores integrated learning to enhance science literacy by engaging students with virus-related materials and prepares students to face future pandemics. This study aims to analyze the effectiveness of multimedia-assisted PBL-SETS in improving students' science literacy about viruses. This study is a quasi-experiment using a one-group pretest-posttest design. The subjects of this study were 40 tenth-grade students at a high school in East Java. This research used a descriptive quantitative methodology that utilised a pre-experimental pretest-posttest design with one group of forty students of class X at a high school in East Java. The PISA 2025 framework was used to develop science literacy tests, while questionnaires assessed students' responses to interactive media. Quantitative and qualitative descriptive analyses were used to analyze the data. The results of the study show that: (1) students' science literacy skills, which were initially 97.5% in the low/very low category, became 47% in the good/very good category; (2) the level of improvement in students' science literacy skills was in the moderate category (n-gain = 0.628); and (3) students' responses to learning were in the good and very good categories. It was concluded that the use of PBL-SETS, supported by interactive multimedia, was effective in improving students' science literacy in the subject of viruses. Further research is recommended in the form of a quasi-experimental study with a larger, more diverse sample and by integrating local wisdom into the development of interactive multimedia.Abstrak. Penelitian ini penting karena mengeksplorasi pembelajaran terpadu untuk melatihkan literasi sains pada materi virus yang lebih menyenangkan dan mempersiapkan siswa untuk menghadapi pandemi di masa depan. Penelitian ini bertujuan untuk menganalisis efektivitas PBL-SETS berbantuan multimedia interaktif untuk meningkatkan literasi sains siswa pada materi virus. Penelitian ini termasuk quasi-eksperimen dengan menggunakan one-group pretest-posttest design. Subyek penelitian adalah 40 siswa kelas X di sebuah SMA di Jawa Timur. Kerangka kerja PISA 2025 digunakan untuk mengembangkan instrumen tes literasi sains, sedangkan kuesioner menilai tanggapan siswa terhadap media interaktif. Analisis deskriptif kuantitatif dan kualitatif digunakan untuk menganalisis data yang didapat. Hasil penelitian menunjukkan bahwa: (1) kemampuan literasi sains siswa yang awalnya 97,5% dalam kategori rendah/sangat rendah menjadi 47% dalam kategori baik/sangat baik; (2) level peningkatan kemampuan literasi sains siswa dalam kategori sedang (n-gain = 0.628); dan (3) respons siswa terhadap pembelajaran dalam kategori baik dan sangat baik. Diperoleh simpulan bahwa penerapan PBL-SETS berbantuan multimedia interaktif adalah efektif untuk meningkatkan kemampuan literasi sains siswa pada materi virus. Penelitian selanjutnya direkomendasikan penelitian kuasi-eksperimen dengan lebih banyak sampel dan beragam.